2001
DOI: 10.1007/s003300100845
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver lesions: MR imaging–pathologic correlation

Abstract: Magnetic resonance signal intensity of focal liver lesions is affected by numerous pathologic factors. Lesion histologic features, such as cellularity, vascularity, stromal component, and intratumoral necrosis or hemorrhage, strongly affect T1 and T2 relaxation times. Additionally, intracellular content of certain substances, such as glycogen, fat, melanin, iron, and copper, may also have a substantial role in determining MR signal behavior. In this review we discuss the correlations between MR imaging feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 88 publications
(102 reference statements)
1
48
1
Order By: Relevance
“…Histopathologic verification was available in 5 cases of focal nodular hyperplasias and 5 cases of hemangiomas. The remaining cases of benign lesions showed typical MRI findings (Horton et al, 1999;Bartolozzi et al, 2001;Bruegel et al, 2008) in conjunction with stability in lesion size and morphology on serial cross-sectional imaging studies with a minimal follow-up interval of 6 months.…”
Section: Patientsmentioning
confidence: 94%
“…Histopathologic verification was available in 5 cases of focal nodular hyperplasias and 5 cases of hemangiomas. The remaining cases of benign lesions showed typical MRI findings (Horton et al, 1999;Bartolozzi et al, 2001;Bruegel et al, 2008) in conjunction with stability in lesion size and morphology on serial cross-sectional imaging studies with a minimal follow-up interval of 6 months.…”
Section: Patientsmentioning
confidence: 94%
“…Areas of calcification in other lesions may also be found, as is the case in HCC, especially in its fibrolamellar variant, owing to central scar calcification (39). Some metastases also have calcifications and consequently low SI on T2-weighted images (29). This has been reported in metastases from mucinous cancers of the colon, stomach, breast, and ovary, as well as in cases of calcified-matrix-producing tumors such as osteosarcomas and chondrosarcomas (38).…”
Section: Calciummentioning
confidence: 95%
“…Various amounts of fibrous tissue are commonly present in several tumors. In fibrolamellar carcinoma, the tumors are formed by abundant fibrosis arranged in bands, or laminae (29,30), which explain their hypointense appearance (Fig 16). The presence of substantial amounts of fibrosis in cholan-giocellular carcinoma explains the presence of the low-SI areas seen on T2-weighted images (Fig 17) (8,9).…”
Section: Fibrosismentioning
confidence: 99%
“…The relationship between FNH and contraceptives is still unclear as several authors have demonstrated that contraceptives may favour FNH progression [19] . The lesion is generally represented by a solid circumscribed mass, sometimes with lobulated contour ( Figure 1), with a central scar surrounded by nodules of hyperplastic hepatocytes and small bile ductuli [20] . FNHs may show a certain degree of histological heterogeneity, due to the variable degree of intra-lesional inflammation, fibrosis or fat content (the latter has been described as steatotic FNH).…”
Section: Evaluation Of Hepatic Adenoma and Focal Nodular Hyperplasiamentioning
confidence: 99%